Have purpose‐built vaccine refrigerators reduced the cost of vaccine losses in South Australia? - Katina D'Onise; Sara Almond; Breda MacDonald; Maureen Watson; Sophie Scrimgeour (Elsevier, 2012)
Abstract Objectives: There is limited epidemiological data on the performance of different refrigerator types for vaccine storage in the real world. This study aims to measure if the introduction of purpose‐built vaccine refrigerators has reduced the cost of vaccine losses in South Australia. Methods: Data were taken from a register for all recorded vaccine storage cold chain events in South Australia from 2008 to 2009 and a survey of vaccine providers conducted in 2009. Results: There were 531 respondents to the survey (51% response rate). A greater proportion of cold chain breaches in purpose‐built vaccine refrigerators did not lead to a loss of vaccine (10.3%) compared with the other refrigerator types. Purpose‐built vaccine refrigerators had a relative risk of 3.31 (95% CI, 2.15-5.11) of a heat event (as opposed to cold event) and were more likely to have a cold chain breach from electrical failure (relative risk ratio 15.05, 95% CI 4.04-56.05) than bar refrigerators. The average cost of loss of vaccine for purpose‐built vaccine refrigerators was $2,321.20, which was greater than the cost of vaccine loss from a bar refrigerator of $1,339.06 (95% CI $61.47-1,902.82). Conclusions: Although purpose‐built vaccine refrigerators were less likely to lead to vaccine loss per cold chain breach, they had a greater average cost of vaccine loss per cold chain event because they held a greater volume of vaccine. There is a need for development of Standards to guide purpose‐built vaccine refrigerators manufacturing and a review of the National Vaccine Storage Guidelines to place a greater emphasis on the need for back up plans in the event of electrical failure.